Methods for the Development of Healthcare Practice Recommendations Using Systematic Reviews and Meta-Analyses - Platz, Thomas (Frontiers in Neurology, 2021)
Quality of healthcare can be improved when the best external evidence available is integrated in clinical decision-making in a systematic explicit manner. With the rapid expansion of clinical evidence, the opportunities for evidence-based high-quality healthcare increase. Paradoxically, the likelihood of any one person to get a complete and balanced picture of the evidence available decreases. This is especially true for rehabilitation interventions that are complex in nature and where clinical research is rather diverse. Given the complex nature of the evidence, there is a substantial risk of misinterpreting the complex information both at the level of individual sources (e.g., reports of clinical trials) and for aggregated data syntheses (e.g., systematic reviews and meta-analyses). These risks are inherent in these sources themselves and are in addition related to the methodological expertise necessary to make valid use of the evidence for clinical decision-making. Taken together, there is a great demand for systematic structured guidance from evidence to clinical decision. This methodology paper describes a structured process for the development and report of evidence-based clinical practice recommendations that uses systematic reviews and meta-analyses as evidence source. It provides a comprehensive framework with specific requirements for the development group, the formulation of the healthcare question addressed, the systematic search for the evidence, its critical appraisal, the extraction and the outcome-centered presentation of the evidence, the rating of its quality, strengths and weaknesses, any further considerations relevant for decision-making, and an explicit recommendation statement along with its justification, implementation, and resource aspects. The suggested methodology uses international standards in evidence synthesis, critical appraisal of systematic reviews, rating the quality of evidence, characteristics of recommendations, and guideline development as developed by Cochrane, GRADE (Grading of Recommendations Assessment, Development and Evaluation), AMSTAR (A MeaSurement Tool to Assess systematic Reviews), and AGREE (Appraisal of Guidelines for REsearch & Evaluation). An added distinctive feature of the methodology is to focus on the most up-to-date, most valid evidence and hence to support the development of valid practice recommendations in an efficient way. Practice recommendations generated by such a valid methodology would be generally applicable and promote evidence-based clinical practice globally.